Effect of training on lactate/ventilatory thresholds: A meta-analysis - Londeree, B. R. (Medicine & Science in Sports & Exercise, 1997)
The purpose of this investigation was to determine the effect of exercise training intensity on lactate and ventilatory thresholds in sedentary and active Ss using meta-analysis procedures. Relatively few longitudinal endurance-training studies have compared the influence of different exercise training intensities upon lactate and/or ventilatory thresholds. The original analyses included 85 study groups from 34 studies.